Analyse du tutorat d’un collectif d’élèves en podologie en école d’application - François-Marie Pelé; Grégory Munoz; Pierre Parage (Éducation et Socialisation)
We present the analysis of the activity of two tutors accompanying simultaneously the learning during the care activity of several learners within a Podology-Pedicuria training institute's application school which welcomes patients in "foot clinic" as well as in private practice. How do the tutors proceed to articulate care activity and learning activity, or according to professional didactics (Pastré, 2011) productive activity and constructive activity? Through a three-step methodology (comprehensive interview, systematic observation and self-confrontation), the analysis of conceptualization in action (Vergnaud, 2007) of tutors allows to determine two pragmatic concepts (Pastré, 2011) what orient their action from a diagnosis of situation that works in dialectical mode.